Information Systems Bedroom Patients Dr. Soeradji Tirtonegoro Klaten - Canggih Ajika Pamungkas; Wahyu Wijaya Widiyanto; Moh Arif Yunianto (International Journal of Computer and Information System (IJCIS), 2021)
RSUP Dr. Soeradji Tirtonegoro Klaten is a hospital that provides several classes of inpatient services. This hospital has 22 inpatient rooms, with a capacity of 409 beds. In the business process, there have been problems where there is no information on the display / picture of the room and bed, the facilities provided, room rates, rooms that are st ill empty and rooms that are already in use, this can result in longer service in registering inpatient care until it requires. time for 20 minutes. The research method that the authors do consists of data collection methods and systems development methods . For the data collection method the author uses the method of observation, interviews, literature study, and documentation. Meanwhile, the system development method that the author uses is the waterfall method with a framework of information systems built using Laravel, the database using MySQL, and for the code editing tool using sublime text. The result of this research is an information system of Dr. Inpatient Bed Room. Soeradji Tirtonegoro Klaten is website-based, the system runs according to its function based on the system test using the blacbox method